ACCESS TO REMEDY FOR VICTIMS OF CORPORATE HUMAN RIGHTS ABUSE: CIVIL LIABILITY LITIGATION IN EUROPE, ENFORCEMENT IN LATIN AMERICA: Civil liability litigation in Europe, enforcement in Latin America - Brackx, Mathilde (Direito.UnB - Revista de Direito da Universidade de Brasília, 2023)
In the challenging search for access to effective remedies for victims of corporate human rights abuse and environmental harm, there has been a growing trend of transnational civil liability litigation before European courts. This trend raises private international law questions regarding the cross-border recognition and enforcement of judgments, which is an essential part of access to justice. Focusing on litigation before European courts ensuing from corporate human rights abuse in Latin America, this article demonstrates the role of rules on recognition and enforcement of foreign judgments in Latin America by providing concrete examples of ongoing cases. Moreover, the suitability of the new 2019 Judgments Convention and of domestic rules on recognition and enforcement for such transnational business and human rights litigation is analyzed. The article demonstrates that the role of cross-border recognition and enforcement rules should not be over- nor underestimated, and that despite a number of shortcomings, the 2019 Judgments Convention can be an important step forward in this regard.